Study of Animal Owners’ Knowledge of Helminthiasis in Cats at Mayda Animal Care and iVet Clinic Dramaga, Bogor - Yusuf, Muhammad Baharudin; Tiuria, Risa; Dewantoro, Galuh Indro (Jurnal Medik Veteriner, 2024)
Animal owners often overlook helminthiasis because it does not cause specific clinical symptoms in mild infections. This study aimed to analyze the medical records of helminthiasis in cats and determine the knowledge of animal owners about helminthiasis through questionnaires at Mayda Animal Care and iVet Clinic Dramaga, Bogor. A cross-sectional study was used to analyze medical record data and then compared using descriptive methods with a secondary data approach. Data analysis was performed using the Chi-square test. The findings of helminthiasis cases in cats at Mayda Animal Care during January–December 2022 amounted to 102 cases, while at iVet Clinic Dramaga, there were 50 cases. Based on the Chi-square test, this study reported a significant correlation (p < 0.05) between age and the level of action and education with the level of understanding of animal owners on helminthiasis at Mayda Animal Care and iVet Clinic Dramaga, Bogor.